Endophytic Fungi as Potential Agents of Helminthosporium sp. in Rice Plant (Oryza sativa L.) - Ratna Eka Sari Putri; Syamsudin Djauhari; Mintarto Martosudiro (Journal of Tropical Plant Protection, 2021)
Brown spot disease is the most serious rice disease due to its destructive nature, wide distribution and presence of several physiological races of the organism. In Asia, the disease has been recorded to reduce crop yields vary broadly from 6-90%. The application of endophytic fungi is reported to increase plant resistance from the secondary metabolites produced. The resulting metabolites are synthesized compounds to maintain their existence in interacting with the environment. The aim of this study was to obtain endophytic fungi of rice plants that were able to suppres Helminthosporium sp. pathogens. Isolation of endophytic fungi was carried out from the roots, peniles, leaves and leaf sheath of rice plants. Identification of endophytic fungi was based on their macroscopic, microscopic characters and molecular identification. Endophytic fungi that had the highest inhibition were T. asperellum, F. nirenbergiae, and F. oxysporum as indicated by the in vitro antagonism test. T. asperellum, F. nirenbergiae, and F. oxysporum also produced IAA hormone between 1.8 to 4.365 mg/L.